Analisis Pengaruh Sektor Unggulan Terhadap Pertumbuhan Ekonomi di Provinsi Pulau Sumatera dan Kalimantan - M Raihan Noer; Armin Rahmansyah Nasution (POLITEKNIK LP3I, 2026)
This research examines how leading sectors shape economic growth across 15 provinces in Sumatra and Kalimantan during 2020–2024, drawing on secondary data from the Central Statistics Agency (BPS). The study incorporates Agriculture, Forestry, and Fisheries (X₁), Mining and Quarrying (X₂), Manufacturing (X₃), and Construction (X₄) as predictors, while Economic Growth (EG) serves as the outcome variable. Two analytical approaches were employed: Location Quotient (LQ) for sector classification and Fixed Effect Model (FEM) panel regression using EViews 12. LQ analysis establishes that all four sectors operate as economic base sectors (LQ > 1) throughout the study area. FEM estimation produces the equation: EG = −1.8124 + 0.1037(X₁) + 0.2941(X₂) + 0.6185(X₃) + 0.8697(X₄). Each variable demonstrates a positive and statistically significant partial effect on growth. Construction emerges as the strongest contributor (β = 0.8697), with Manufacturing (β = 0.6185), Mining and Quarrying (β = 0.2941), and Agriculture (β = 0.1037) ranking subsequently. The joint significance test confirms simultaneous influence of all sectors (p = 0.0000), with R² = 0.9094, indicating that the model accounts for 90.94 percent of the variation in inter-regional economic growth.